DERMATOPHYTOSIS IN MIXED BREED DOG - Pratama, I Gede Made Andy; Widyastuti, Sri Kayati; Batan, I Wayan (Buletin Veteriner Udayana, 2023)
Dermatophytosis is a skin disease caused by dermatophytes yeast. The purpose of examining the case dogs is to determine the agent of the disease that causes many lesions on the dog's skin. The case dog was brought to the Pedungan Vet Care clinic with complaints of skin problems that had been occurring for one month. the case dog is a mixed breed dog aged about one year with a body weight of 12.2 kg and is a rescued dog. On clinical examination there were abnormalities such as lesions consisting of a combination of alopecia, erythema, and crusts. The lesions were found on the ear, face, hind limb, pelvic limb, abdomen, and dorsal part of the body. Then the parts of the lesion were scraped at the edges of the lesion using 10% KOH and a swab. From the results of skin scrapings, the results were negative for dermatophytes. The Wood's lamp examination was negative. On tape smear examination, macroconidia were found in the form of elliptical which were divided into several cells, indicating a positive result of Microsporum sp. Based on the history, physical examination, clinical examination, and laboratory, it can be said that the disease is dermatophytosis. Case dogs were given causative and symptomatic therapy, for causative therapy griseofulvin was given at a dose of 500 mg/kg/bb q.12 hours orally and symptomatic therapy was given the antihistamine chlorpheniramine maleate at a dose of 4 mg/kg/bb q.12 hours orally for 14 days, antiseptic chlorhexidine gluconate 0.05% for cleaning wounds twice a day, and case dogs were bathed with Sebazole ® antifungal shampoo twice a week for one month. After seven days of treatment, the pruritus symptoms observed decreased but there were no significant changes for other diseases.